(untitled) (Andamios, Revista de Investigación Social, 2012)
This essay seeks to visit policy process and policy change literature, in order to identify theoretical tendencies through several typology proposals of policy change based both old and current orthodoxies, and used in determining what is policy change, and linked, how change occurs.